Aplikasi Inventory Control Pada Multistore CV.Plastik - Tommy Hartanto Salim; Andreas Handojo; Djoni Haryadi Setiabudi (Jurnal Infra, 2020)
The need for information in this era of globalization needed a breakthrough that could facilitate the acquisition of information, along with the various methods done to develop knowledge and information in Inventory Control. He did this research because of the stock information on CV. Plastic is not managed properly, so often the buildup of goods in the warehouse CV. Plastic, as well as uncomputerised stock logging.Inventory Control system using Fixed Order Quantity (FOQ) and forecasting method, can help to manage information in stock logging, assist in the operation of stock transaction in stock order, stock procurement, storage Stock, and stock mutation, and to support the sales process on CV. Plastic.The results of the research indicated by the calculation of FOQ, safety stock, and ROP can be used to prevent excess stock, lost stock, damaged stock and anticipate out of stock. Forecasting that can be used is trend forecasting because it has only error 6%.